The correlation between spirituality and adherence in diabetes mellitus type 2 patients - Adang Muhammad Gugun; Yusuf Alam Romadhon; Dwi Marlina Putri; Suci Aprilia (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2022)
Background: The adherence of type 2 diabetes mellitus (DM) patients plays an important role in therapeutic management. In carrying out every activity, a Muslim must make spirituality as a reference. Therefore, it is necessary to study the relationship of spirituality in type 2 DM patients with diabetes mellitus medication adherence. Objective: Estimate the correlation between spirituality and patients’ type 2 DM adherence.Methods: This study was observational with a cross-sectional design at PKU Muhammadiyah Gamping Hospital. Subjects were patients with type 2 diabetes mellitus. The level of spirituality was obtained using the Holistic Health Care (HHC) questionnaire and adherence was using the Summary of Diabetes Self-Care Activities (SDSCA) questionnaire. There were 70 subjects between 35-73 years, 40 women and 30 men. The data were analysed using the Somers’ D test to determine the correlation. Results: From 70 subjects, the spirituality level was 68.6% nirvana, guide 14.3%, sorrow 12.9% and revive 4.3%. The acceptance score obtained was 82.0% positive and 17.1% negative. The obedient score obtained was 72.9% positive and 27.9% negative. The level of patient adherence was very high at 44.2%, high at 12.9%, moderate at 20%, low at 10%, and very low at 12.9%. There was no correlation between acceptance scores and patient adherence level (r = 0.185, p-value = 0.299), on the contrary, there was a correlation between obedient scores and patient adherence levels (r = 0.34, p-value = 0.021). There is a significant correlation between the total spirituality score and patient adherence (r = 0.262, p-value = 0.035). Conclusion: There is a correlation between spirituality and type 2 DM patients’ adherence.